(untitled) (Hekima Review, 1994)
I do not deny that we need to have confidence in God, but does dependence on God mean expecting God to do things in the place of man? I am not against forgiveness and reconciliation but can pardon be granted to African dictators who refuse to recognize their numerous crimes and apologise for them? I agree that no one is to be excluded from God's love but how do I love the rich and the poor in a continent where those who have and those who do not have live in two separated worlds? I want, in the present essay, to suggest a rediscovery of trust, forgiveness and love in the understanding and life of Jesus.